FUNGAL SPORE SEDIMEN RESEN DELTA FRONT DELTA MAHAKAM KALIMANTAN TIMUR - -, Winantris (Fakultas Teknik Geologi Universitas Padjadjaran, 2011)
Ten samples taken from delta front by grab sampler. Sediment grain size of delta front varies from fine silt to fine sand. Acetolyzed method was used to separate fungal spore from sediment. Two methods used to identify of fungal spore i.e. Elsik classifications and fungal classification. Fungal spores in delta front derived from terrestrial and marine. Fungal spore is effective to study deposition environment and paleoenvironment.